A brief account of nanoparticle contrast agents for photoacoustic imaging. (23rd August 2013) - Pan, Dipanjan; Kim, Benjamin; Wang, Lihong V.; Lanza, Gregory M
Abstract : Photoacoustic imaging (PAI) is a hybrid, nonionizing modality offering excellent spatial resolution, deep penetration, and high soft tissue contrast. In PAI, signal is generated based on the absorption of laser‐generated optical energy by endogenous tissues or exogenous contrast agents leading to acoustic emissions detected by an ultrasound transducer. Research in this area over the years has shown that PAI has the ability to provide both physiological and molecular imaging, which can be viewed alone or used in a hybrid modality fashion to extend the anatomic and hemodynamic sensitivities of clinical ultrasound. PAI may be performed using inherent contrast afforded by light absorbing molecules such as hemoglobin, myoglobin, and melanin or exogenous small molecule contrast agent such as near infrared dyes and porphyrins. However, this review summarizes the potential of exogenous nanoparticle‐based agents for PAI applications including contrast based on gold particles, carbon nanotubes, and encapsulated copper compounds. WIREs Nanomed Nanobiotechnol 2013, 5:517–543. doi: 10.1002/wnan.1227 This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging